Estrategias digitales de comunicación externa para posicionar la imagen Corporativa de la Cooperativa de Ahorro y Crédito Guaranda Ltda., cantón Guaranda, año 2023 - Lara Fuentes, Anyela Stefania (2023)
The present study aims to analyze the importance of external communication strategies in positioning the corporate image of Cooperativa de Ahorro y Crédito Guaranda Ltda., located in the Guaranda canton in the year 2023. To achieve this, a descriptive and exploratory methodology was proposed. Information was gathered through surveys applied to employees and customers of the cooperative, as well as interviews with communication experts. A random sampling was used to obtain a representative sample of the population. The main results show that the cooperative faces challenges in its external communication, especially in terms of transparency and clarity in the information provided to customers. Areas for improvement were also identified in customer service and emotional connection with the audience. On the other hand, the importance of internal communication in the coherence and consistency of the corporate image was highlighted. As conclusions, it was found that an effective external communication strategy is crucial for positioning the corporate image in the financial market. It is recommended to implement an external communication plan that addresses the identified areas for improvement and utilizes digital strategies to promote the cooperative's value proposition. Likewise, improving internal communication is suggested to strengthen the cohesion of the corporate image. Continuous evaluation through indicators will allow measuring the impact of the external communication strategy and ensuring the success and continuous improvement of the plan. Keywords: External Communication, Corporate Image, Digital Strategies, Cooperativa De Ahorro Y Crédito, Market Positioning.